Maieutic method and philosophical consulting in the 21st Century - Romero Vela, Sonia (2019)
Philosophical research requires more studies in the metaphysical field of man as a single entity in order to carry out a line or project of life in this world. The research presents Philosophy as a practice of life based on the contributions of Socrates, a Greek philosopher, aims to analyze the importance of the majestic method in the human condition in philosophical consultancies in this century. The study is qualitative, interpretive design. Within the materials we have worked with bibliographic research through the reading and signing of the texts of Plato and Aristotle. The Socratic method is important in philosophical consultancies because humanity is in existential risk as a result of various factors that overwhelm daily activities such as social, ethical, axiological risks, individualism, global warming, environmental pollution and others.